Sedentarism and Metabolic Syndrome: Broadening the measurement of sedentarism - Lucélia Cunha Magalhães; Silva DO; Araújo MJ; RN Lessa I; Almeida Filho N; Aquino EML (Archives of Community Medicine and Public Health - Peertechz Publications, 2019)
The metabolic syndrome (MS) is a combination of cardiovascular risk factors, including visceral obesity, low HDL cholesterol level, increased triglycerides, hyperglycemia and high blood pressure. This sequence of risk factors contributes towards the development of atherosclerotic cardiovascular disease (ACVD) and diabetes mellitus. Sedentarism is not widely studied. This habit is a determinant factor for chronic or acute diseases. This study tests the hypothesis of the association between overall sedentarism, including professional work, travel and leisure and the MS, in adult men and women in Salvador, Bahia.